2014
DOI: 10.1371/journal.pone.0108272
|View full text |Cite
|
Sign up to set email alerts
|

Production of the Catechol Type Siderophore Bacillibactin by the Honey Bee Pathogen Paenibacillus larvae

Abstract: The Gram-positive bacterium Paenibacillus larvae is the etiological agent of American Foulbrood. This bacterial infection of honey bee brood is a notifiable epizootic posing a serious threat to global honey bee health because not only individual larvae but also entire colonies succumb to the disease. In the recent past considerable progress has been made in elucidating molecular aspects of host pathogen interactions during pathogenesis of P. larvae infections. Especially the sequencing and annotation of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 78 publications
0
38
0
Order By: Relevance
“…It is about 11 kb in length, consists of five genes, and shows strong homology to the bacillibactin gene clusters of Bacillus subtilis and the B. cereus sensu lato group as well as to the paenibactin gene cluster of Paenibacillus elgii, [17 ,36 ]. Mass spectrometric fragmentation analyses confirmed that the NRPS machinery is responsible for the production of the catechol-type siderophore bacillibactin (Dhb) in P. larvae [36 ]. Production of Dhb by P. larvae could only be demonstrated in culture under iron limited conditions.…”
Section: Identification and Role Of Secondary Metabolitesmentioning
confidence: 96%
See 1 more Smart Citation
“…It is about 11 kb in length, consists of five genes, and shows strong homology to the bacillibactin gene clusters of Bacillus subtilis and the B. cereus sensu lato group as well as to the paenibactin gene cluster of Paenibacillus elgii, [17 ,36 ]. Mass spectrometric fragmentation analyses confirmed that the NRPS machinery is responsible for the production of the catechol-type siderophore bacillibactin (Dhb) in P. larvae [36 ]. Production of Dhb by P. larvae could only be demonstrated in culture under iron limited conditions.…”
Section: Identification and Role Of Secondary Metabolitesmentioning
confidence: 96%
“…Production of Dhb by P. larvae could only be demonstrated in culture under iron limited conditions. Larval infection assays performed with gene inactivation mutants of P. larvae (DdhbF) and the corresponding wild-type strain did not give any hints for a role of Dhb during pathogenesis: neither total mortality nor disease progression were affected by the absence of Dhb production [36 ]. However, the experimental design did not allow to test whether the lack of Dhb production had any effect on the growth of other bacteria like P. alvei.…”
Section: Identification and Role Of Secondary Metabolitesmentioning
confidence: 99%
“…These multienzyme complexes consist of various modules that each incorporate one or more specific amino acids into a peptide backbone (see also “Nonribosomal lipopeptides” section). The three types of siderophores are classified based on their functional groups, being catecholates, hydroxamates, and α-hydroxy carbolates [38]. However, few siderophores have thus far been characterized from Paenibacillus .…”
Section: Plant Growth Promotionmentioning
confidence: 99%
“…Paenibacillus larvae produces a catecholate -type siderophore called bacillibactin, which is also made by Bacillus subtilis and members of the Bacillus cereus sensu lato group [38]. Bacillibactin is a cyclic trimeric lactone of 2,3-dihydroxybenzoate (DHB)-glycine-threonine.…”
Section: Plant Growth Promotionmentioning
confidence: 99%
See 1 more Smart Citation